2017
DOI: 10.1016/j.neuron.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Oppositely Oriented Microtubules Controls Polarized Neuronal Transport

Abstract: SummaryMicrotubules are essential for polarized transport in neurons, but how their organization guides motor proteins to axons or dendrites is unclear. Because different motors recognize distinct microtubule properties, we used optical nanoscopy to examine the relationship between microtubule orientations, stability, and modifications. Nanometric tracking of motors to super-resolve microtubules and determine their polarity revealed that in dendrites, stable and acetylated microtubules are mostly oriented minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
335
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(352 citation statements)
references
References 57 publications
(96 reference statements)
17
335
0
Order By: Relevance
“…In dendrites, no kinesins labeled vesicles with a strong directionality preference (Figure B). This is consistent with the mixed orientation of dendritic microtubules, which could enable kinesins to mediate both anterograde and retrograde transport …”
Section: Resultssupporting
confidence: 84%
“…In dendrites, no kinesins labeled vesicles with a strong directionality preference (Figure B). This is consistent with the mixed orientation of dendritic microtubules, which could enable kinesins to mediate both anterograde and retrograde transport …”
Section: Resultssupporting
confidence: 84%
“…A parsimonious explanation is that SEPT9 marks and/or bridges MTs of plus-end-out orientation. While this article was under review, it was reported that kinesin-1/KIF5 associates preferentially with acetylated MTs of minus-end-out orientation and kinesin-3/KIF1A interacts with dynamic tyrosinated MTs, which are oriented with their plus ends out (Tas et al, 2017). Hence, SEPT9 may have a role in the regulation of membrane traffic on the plus-end-out subsets of MTs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, KIF3AB is ubiquitously expressed including neurons (2-4, 34), but our best understanding of KIF3AB transport is for intraflagellar transport in cilia. One testable hypothesis for future investigation is whether KIF3AC and KIF3AB in neurons read the tubulin code differently based on posttranslational modifications of the axonal versus dendritic microtubules to bias selective transport of cargos to enter axons or dendrites (34,(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, KIF3AB is ubiquitously expressed including neurons (2-4, 34), but our best understanding of KIF3AB transport is for intraflagellar transport in cilia. One testable hypothesis for future investigation is whether KIF3AC and KIF3AB in neurons read the tubulin code differently based on posttranslational by guest on April 27, 2019 http://www.jbc.org/ Downloaded from 9 modifications of the axonal versus dendritic microtubules to bias selective transport of cargos to enter axons or dendrites (34,(53)(54)(55).In summary, mathematical modeling has provided new insights to understand the motile properties of KIF3AC and KIF3AB. These results revealed that microtubule association for KIF3AC and KIF3AB is an emergent property due to heterodimerization, and once in the processive run, the rates of the nucleotide-dependent transitions result from the relative intrinsic catalytic properties of the motor domains.…”
mentioning
confidence: 99%